Neurobiological Determinants of Tobacco Smoking in Schizophrenia - Lucatch, Aliya M.; Lowe, Darby J. E.; Clark, Rachel C.; Kozak, Karolina; George, Tony P. (Frontiers in Psychiatry, 2018)
Purpose of review: To provide an overview of the underlying neurobiology of tobacco smoking in schizophrenia, and implications for treatment of this co-morbidity. Recent findings: Explanations for heavy tobacco smoking in schizophrenia include pro-cognitive effects of nicotine, and remediation of the underlying pathophysiology of schizophrenia. Nicotine may ameliorate neurochemical deficits through nicotine acetylcholine receptors (nAChRs) located on the dopamine, glutamate and GABA neurons. Neurophysiological indices including electroencephalography, electromyography, and smooth pursuit eye movement paradigms may be biomarkers for underlying neuronal imbalances that contribute to the specific risk of tobacco smoking initiation, maintenance and difficulty quitting within schizophrenia. Moreover, several social factors including socioeconomic factors and permissive smoking culture in mental health facilities, may contribute to the smoking behaviours (initiation, maintenance and inability to quit smoking) within this disorder. Summary: Tobacco smoking may alleviate specific symptoms associated with schizophrenia. Understanding the neurobiological underpinnings and psychosocial determinants of this comorbidity may better explain these potential beneficial effects, while also provide important insights into effective treatments for smoking cessation.